Gdf15 deletion exacerbates acute lung injuries induced by intratracheal inoculation of aerosolized ricin in mice. (15th March 2022) - Deng, Mengyun; Su, Duo; Xiao, Nan; Zhang, Zhipeng; Wang, Yifeng; Zong, Fuliang; Li, Sha; Wang, Jinglin; Zhou, Dongsheng; Zhao, Yuee; Yang, Huiying
Abstract: Ricin toxin (RT) is a potent toxin derived from castor beans and has a high risk of mortality following inhalation-induced acute lung injury (ALI). Growth differentiation factor 15 (GDF15) is a member of the transforming growth factor β superfamily and acts as a protective effect in diverse inflammatory diseases. Yet, the role of GDF15 in ALI has not been evaluated. In this study, we investigated the intrinsic role of Gdf15 in ALI induced by intratracheal inoculation of a 1.5 × LD50 (lethal dose for 50%) of aerosolized RT in Gdf15 knockout (KO) mice compared to wild-type (WT) mice. In this model, Gdf15 deletion significantly increased pathology in lung tissues for RT-induced ALI in mice, led to significantly decreased body weights and survival rates and increased expression of inflammatory-related cytokine and chemokine levels at 24 and 72 h post-exposure. Infiltration of myeloid cells in lung tissue were quantified using flow cytometry. Although a similar infiltration pattern of inflammatory cells was observed in Gdf15 KO and WT groups, Gdf15 KO mice had elevated levels of neutrophils and decreased levels of Ly6C lo monocytes (cells with distinct destructive and protective roles, respectively) in the early stage of ALI. Gene expression profiles revealed similar effects as observed through RNA-seq. Bioinformatics analysis confirmed that pro-inflammatory signaling pathways were activated and the expression of inflammatory genes was significantly up-regulated after RT exposure compared to the corresponding baseline control in Gdf15 KO and WT mice. Compared to WT mice, inflammatory genes were more pronounced in Gdf15 KO groups after RT exposure. To our knowledge, this study presents the first research to systematically evaluate the role of Gdf15 in RT-induced ALI. These results collectively uncovered an immune response signature in lung tissues and reveal a critical role of Gdf15 in this ALI mice model. Our findings expose novel opportunities to investigate the contribution of GDF15 for the treatment of lung inflammatory diseases. Graphical Abstract: ga1 Highlights: Gdf15 deletion exacerbates lung pathological damage after ricin exposure. Gdf15 deletion leads to increased expression of inflammation-associated cytokines. Gdf15 deletion alters immune cell infiltration and accumulation in the lung. Gdf15 deletion increases NF-κB activity and upregulates inflammatory genes.